Implications of the Communication Technology Revolution in Education and Society of Indonesia - Asrori, Achmad; Nasor, Nasor; Hakim, Dani Amran; Puspitasari, Nina Ayu; Anggraini, Heni; Anum, Adelina (CV. Tripe Konsultan, 2024)
The communication revolution is growing in the assumption that communication is a vital element in human life. The problem that emerges in the use of communication technology is the perception of the Indonesian people that the social, educational, and economic spheres of technology are regarded as tools that can solve the problems of this world of life easily without paying attention to the effects of these three areas. Industry implications in the field of communications technology are significant for social life, economic growth, and educational dynamics in Indonesia, but also have a threat of negative impacts that are difficult to avoid. The industrialization of the media is increasingly demonstrating how much society and all aspects connected with it, including social, economic, and educational aspects, are in need of information through mass media technology that is growing so rapidly in the age of globalization.